Religion, spirituality, and older adults with HIV: critical personal and social resources for an aging epidemic - Vance D (Dove Medical Press, 2011)
David E Vance1, Mark Brennan2, Comfort Enah1, Glenda L Smith1, Jaspreet Kaur31School of Nursing, University of Alabama at Birmingham (UAB), Birmingham, AL, USA; 2New York University College of Nursing, AIDS Community Research Initiative of America, New York, NY, USA; 3Department of Psychology and Edward R. Roybal Center for Translational Research in Aging and Mobility, University of Alabama at Birmingham (UAB), Birmingham, AL, USAAbstract: By 2015, approximately half of adults with HIV in the United States will be 50 and older. The demographic changes in this population due to successful treatment represent a unique challenge, not only in assisting these individuals to cope with their illness, but also in helping them to age successfully with this disease. Religious involvement and spirituality have been observed to promote successful aging in the general population and help those with HIV cope with their disease, yet little is known about how these resources may affect aging with HIV. Also, inherent barriers such as HIV stigma and ageism may prevent people from benefitting from religious and spiritual sources of solace as they age with HIV. In this paper, we present a model of barriers to successful aging with HIV, along with a discussion of how spirituality and religiousness may help people overcome these barriers. From this synthesis, implications for practice and research to improve the quality of life of this aging population are provided.Keywords: HIV, aging, spirituality, religion, stigma, coping, successful aging